Sexual Dysfunctions among Diabetic and Non-diabetic People Attending in Tribhuvan University Teaching Hospital, Kathmandu Nepal - Karki, Khem Bahadur; Shah, Bhupendra Kumar; Shrestha, Sushan Man (Journal of Nepal Health Research Council, 2024)
Background: Sexual dysfunctions including erectile dysfunction among men, a widespread sexual health issue, pose challenges to sexual satisfaction. This cross-sectional study aimed to assess the prevalence and determinants of sexual dysfunctions in both diabetic and non-diabetic individuals aged 30-70. Methods: A study at Tribhuvan University Teaching Hospital in Kathmandu, Nepal, surveyed 350 participants (176 men, 174 women), aged 30-70, with 52.6% having diabetes. The structured interviews and validated questionnaires like IIEF-5 for men and FSFI-6 for women to assess the prevalence and factors associated with erectile dysfunction were used. Statistical tools were employed to measure the associations of different variables with Sexual dysfunctions. Results: Overall, the prevalence of sexual dysfunction was 73.7% (95% CI: 72.4- 73.7) with higher rates in men 83.9% (95% CI: 83.1- 84.7) than women 63.6% (95% CI: 62.0 - 65.2). Individuals with diabetes experienced an 81.5% prevalence of sexual dysfunction (95% CI: 80.6-82.4), whereas non-diabetic individuals exhibited a 65.1% prevalence (95% CI: 63.5-66.7). In the diabetic male population, the prevalence of sexual dysfunction was 97.5% (95% CI: 97.4-97.6), while diabetic females had a prevalence of 68.9% (95% CI: 67.5-70.3). Among non-diabetic men, the percentage of erectile dysfunction was 72% (95% CI: 70.7-73.3), and among non-diabetic women, sexual dysfunction remained 56.2% (95% CI: 54.4-58.0). Among individuals with diabetes, those who used tobacco exhibited a sexual dysfunction prevalence of 93.8% (95% CI: 93.5-94.1), while non-tobacco users had a prevalence of 74.8% (95% CI: 73.6-76.0). In non-diabetic individuals, obesity was associated with a higher prevalence of sexual dysfunctions, reaching 84.6% (95% CI: 83.8-84.6). High blood pressure showed a strong association with sexual dysfunctions in both diabetic (83% with 95% CI: 81.9-83.4) and non-diabetic (70% with 95% CI: 67.7-70.1) groups. Individuals with diabetes for more than five years had a higher rate of sexual dysfunction as 87.8% (95% CI: 86.6-89.0) with 100% in men and 79% in women. However, there was no significant difference in the prevalence of sexual dysfunctions related to obesity and alcohol consumption between diabetics and non-diabetics. Conclusions: The research highlights a noteworthy association of sexual dysfunctions with individuals with diabetes, male sex, tobacco use, and hypertension. The observed high prevalence of sexual dysfunctions in both diabetic and non diabetic people is a public health concern, emphasizing the need for culturally tailored approaches to address the sexual health of the affected individuals. Keywords: Diabetes; hypertension; lifestyle factors; sexual dysfunctions.